Design and Develop Of A Web-Based Information System Employee Performance Appraisal At BKKBN East Jakarta - Yustrianda, Nugraha Dwi; Sudarsono, Bernadus Gunawan; Sharyanto, Sharyanto (Journal of Engineering, Technology and Computing (JETCom), 2025)
BKKBN focuses on population planning and management in order to achieve a better quality of life for the people of Indonesia. This research aims to design and implement a web-based employee performance appraisal information system at the East Jakarta National Population and Family Planning Agency (BKKBN). This system is developed to facilitate the process of employee performance appraisal more efficiently, transparently, and accurately. The main features of this system include managing employee data, performance appraisal forms, processing appraisal results, and reporting and analyzing performance. The system design uses the waterfall software development method, starting from requirements analysis, system design, implementation, to the testing stage. The system is designed to be accessible by management and employees through a user-friendly web interface, thus facilitating the periodic performance evaluation process. The implementation results show that this system succeeds in improving accuracy and efficiency in the performance appraisal process, as well as providing data that is more structured and easily accessible by related parties.